Developing mathematical literacy problems using Jogja tourism context - Istihapsari, Vita; Istiandaru, Afit (International Journal on Education Insight, 2025)
The Indonesian performance in PISA mathematics consistently low in the last decade, despite the increasing awareness among mathematics educators regarding the importance of mathematical literacy. One of the core problems is the lack of mathematical literacy problems while the resources of contexts are available and rich. This research aims to develop a set of mathematical literacy problems using Jogja tourism context. It is an ADDIE research which includes the analysis, design, develop, implementation, and evaluation stage. We involved two mathematics educators as the experts to validate the problems and 441 junior high school students in Yogyakarta to try-out the problems. Finally, we successfully developed 35 valid items of mathematical literacy problems with Jogja tourism context in terms of content and construct. The availability of these word problems would be useful for mathematics educators to foster the students’ mathematical literacy at school.